Revisión Sistemática De La Correlación De La Maduración De Las Vértebras Cervicales (Método Baccetti) Y La Osificación De La Sutura Media Palatina (Método Angelieri) - Silva Guerra, Jeimmi Patricia; Mesa Benítez, Carlos Eduardo (Universidad Antonio Nariño, 2022)
To establish the correlation between the maturation of the cervical vertebrae and the ossification of the midpalatal suture by means of a systematic review.